Description of the larvae of Drusus ramae Marinković-Gospodnetić and Drusus medianus Marinković-Gospodnetić (Trichoptera: Limnephilidae) with some genetic, distributional, ecological, faunal and conservation notes - Kučinić, Mladen; Previšić, Ana; Stanić-Koštroman, Svjetlana; Franjević, Milivoj; Jelaska, Lucija Šerić; Delić, Antun; Posilović, Hrvoje (Zootaxa, 2010)
In this study we present morphological features of the last instar larvae of Drusus ramae Marinković-Gospodnetić, 1971, and Drusus medianus Marinković-Gospodnetić, 1976, both of which are endemic species from Bosnia and Herzegovina. Using the mitochondrial cytochrome oxidase I gene (COI), larvae of these species were successfully associated with adult specimens. We present the most important diagnostic features enabling separation from larvae of the other Drusus species and an identification key for the known larvae of Drusus species in the Balkan Peninsula. Notes on the distribution and ecology of both species are given. Additionally, faunistics and possible conservation implications for studied springs are discussed.